Interactive effects of locus coeruleus structure and catecholamine synthesis capacity on cognitive function - Chen, Hsiang-Yu; Parent, Jourdan H.; Ciampa, Claire J.; Dahl, Martin J.; Hämmerer, Dorothea; Maass, Anne; Winer, Joseph R.; Yakupov, Renat; Inglis, Ben; Betts, Matthew J.; Berry, Anne S. (Frontiers in Aging Neuroscience, 2023)
The locus coeruleus (LC) produces catecholamines (norepinephrine and dopamine) and is implicated in a broad range of cognitive functions including attention and executive function. Recent advancements in magnetic resonance imaging (MRI) approaches allow for the visualization and quantification of LC structure. Human research focused on the LC has since exploded given the LC's role in cognition and relevance to current models of psychopathology and neurodegenerative disease. However, it is unclear to what extent LC structure reflects underlying catecholamine function, and how LC structure and neurochemical function are collectively associated with cognitive performance. We applied partial least squares correlation (PLSC) analysis to 19 participants' LC structural MRI measures and catecholamine synthesis capacity measures assessed using [ 18 F]Fluoro-m-tyrosine ([ 18 F]FMT) positron emission tomography (PET). We found no direct association between LC-MRI and LC-[ 18 F]FMT measures for rostral, middle, or caudal portions of the LC. We found significant associations between LC neuroimaging measures and neuropsychological performance that were driven by rostral and middle portions of the LC, which is in line with LC cortical projection patterns. Specifically, associations with executive function and processing speed arose from contributions of both LC structure and interactions between LC structure and catecholamine synthesis capacity. These data leave open the possibility that LC MRI and PET measures contribute unique information and suggest that their conjoint use may increase sensitivity to brainbehavior associations in small samples.